Bahasa Anak Usia Tiga Tahun di TK Raodah - Nurlatifah Khairiyah; Juanda Juanda (FKIP UNILA, 2023)
The Language of Three-Year-Old Children in Kindergarten Raodah. Language acquisition in early childhood is a golden period that greatly determines the development of child psychology. Many parents do not know about the language acquisition barriers that may occur in their children so that language acquisition barriers are not handled early on. Therefore, research on language acquisition in children aged 3 years is very interesting to do. This study aims to determine children's language acquisition at the level of phonology, syntax, and sematics including respondents who are able to speak well, there is no difference in speech. This research uses descriptive method with qualitative analysis techniques. Data collection was carried out in three ways, namely observation, interview, and documentation techniques. The researcher observed the subject's language about language acquisition at three levels, namely the level of phonology, syntax and semantics. To support the data, the researcher conducted interviews with the research subjects and to further clarify the data, the researcher conducted documentation techniques on the subject. The results of this study indicate that respondents can speak quite well, and there are no significant deviations in the resulting speech. Language acquisition experienced by children aged 3 years is at the stage of sentence development. The subject already knows the pattern of speech and already knows when it is his turn to speak. Respondents have learned adult written language, their language is improving and their phonological development is successful. However, respondents still have difficulty pronouncing various consonants. This research can be used as a source of knowledge and information about children's language acquisition to avoid an attitude of not wanting to know which will result in the loss of children's language acquisition process.Keywords: language acquisition, phonology, semantics, syntax